(3GdEWGQ GdacQj hGdfXe GdJWHjbjI GdfXGe GdjOhj(B-(3JMdjd hJUeje GdfXGe(B-(3fXGe GdeMGSHIs - (3CMeO MSjf Ydj(B, (3MSjfs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2003)
(3fXe GdeYdheGJ GdeMGSHj GdjOhj(B-(3JMdjd hJUeje hJfajP GdfXe(B-(3fXGe GdeMGSHj aj HjFI GdeMGSHIs
Keywords: (3GdeMGSHIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s